Lovell-Troy & Eickmann, Course Design For College Teachers - Brown, Robert (Teaching History: A Journal of Methods, 1992)
Concern about the quality of undergraduate education at American colleges and universities has been mirrored by the publication of handbooks on teaching and instructional design, such as Course Design for College Teachers. According to Larry Lovell-Troy, Associate Professor of Sociology at Millikin University and principal author, this guide and workbook originated from ideas advanced first by Paul Eickmann at the Syracuse University Center for Instructional Development and then refined over more than a decade in a Workshop on Course Design and Teaching sponsored by the Great Lakes Colleges Association.